Body and Mind in Abhidhamma and Descartes - Choosukhserm, Thanakorn (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
The objectives of this article were to study: 1) body and mind in Abhidhamma and Descartes viewpoint and 2) similarity and difference of body and mind of both viewpoints. From this study, it was found that body and mind in Abhidhamma and Descartes viewpoint had both similar and different characteristics. The similarity of both body and mind was each one separated their functions but depended on each other, could not definitely separate it from each other. The body is the material or Rupa can be seen, touched experienced and the extended thing. But the mind of both viewpoints has similarity: it is norm or abstract, untouchable and can work independently from the body. But the different characteristics of the body and mind in Abhidhamma and Descartes are: the body in Abhidhamma is from Kamma comprising of the 4 elements, but the body in Descartes’ viewpoint is from the substance or being itself, does not depend on other thing that is the human being’s body. It is extended thing but does not have thinking. The different characteristics of mind in Abhidhamma and Descartes’s viewpoint are: the mind in this text is the object-knowing, object is the known thing by mind, has its independence, does temporarily happen and decay but the mind in Descartes’s viewpoint means the thinking thing or thought. It has stable being, unchangeable, but functions itself by the power of God. Mind always has to think and has also the thinking thing that is the idea. Every idea causes to make me happen as his speech “I think therefore, I am.”